Study on Characteristic Strength of Concrete Partially Replaced by Geopolymer Aggregates - George, Geena; Asha, K. (AMC Indian Journal of Civil Engineering, 2019)
Huge amount of quarrying for extraction of natural aggregates has reached an alarming situation which affects the ecological balance. Also, unscientific disposal of industrial wastes is creating problems. An attempt is made to use industrial wastes such as Flyash and Ground-granulated blast-furnace slag (GGBS) for manufacturing artificial aggregates using geopolymerization technique as an alternative for natural aggregates. This study concentrates on the partial replacement of characteristic coarse aggregates with geopolymer fly ash aggregates. Factors affecting the strength of geopolymer flyash aggregates such as geopolymer solids ratio, concentration of alkali activator, and curing period were evaluated. Various ratios of Flyash and GGBS such as 90:10, 25:75, and 50:50 were mixed to make geopolymer solids. The fundamental physical properties and mechanical attributes of geopolymer fly ash aggregates are studied. The characteristic strength of partially replaced geopolymer aggregate concrete was understood. It is observed that upto 30-35 % replacement of the strength can be compared to normal concrete, and after that there is a considerable decrease. By conducting Scanning Electron Microscopy (SEM), and X-Ray Diffraction (XRD analysis), micro-structural study of geopolymer fly ash aggregates is also done.